2014
DOI: 10.1186/2050-7283-2-22
|View full text |Cite
|
Sign up to set email alerts
|

Rumination and interoceptive accuracy predict the occurrence of the thermal grill illusion of pain

Abstract: BackgroundWhile the neurophysiological mechanisms underlying the thermal grill illusion of pain (TGI) have been thoroughly studied, psychological determinants largely remain unknown. The present study aimed to investigate whether cognitive and affective personality traits encompassing rumination, interoception, and suggestibility may be identified as characteristics favouring the elicitation of paradoxical pain experiences.MethodsThe dominant hand of 54 healthy volunteers was stimulated with a water-bath drive… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
24
1

Year Published

2016
2016
2025
2025

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 25 publications
(28 citation statements)
references
References 79 publications
3
24
1
Order By: Relevance
“…Correspondingly, people with higher interoceptive accuracy on heartbeat detection tasks report a greater intensity of emotional experience (Pollatos, Traut-Mattausch, Schroeder, & Schandry, 2007;Wiens, Mezzacappa, & Katkin, 2000). Moreover, individual differences in interoception influence vulnerability to both physical and psychological symptoms (Dunn et al, 2010;Schaefer, Egloff, Gerlach, & Witthoft, 2014;Scheuren, Sutterlin, & Anton, 2014). Together, these findings support the proposal that detection of bodily sensations can shape emotional and affective experience.…”
supporting
confidence: 73%
“…Correspondingly, people with higher interoceptive accuracy on heartbeat detection tasks report a greater intensity of emotional experience (Pollatos, Traut-Mattausch, Schroeder, & Schandry, 2007;Wiens, Mezzacappa, & Katkin, 2000). Moreover, individual differences in interoception influence vulnerability to both physical and psychological symptoms (Dunn et al, 2010;Schaefer, Egloff, Gerlach, & Witthoft, 2014;Scheuren, Sutterlin, & Anton, 2014). Together, these findings support the proposal that detection of bodily sensations can shape emotional and affective experience.…”
supporting
confidence: 73%
“…Psychological mechanisms may moreover be considered as relevant factors contributing to the association between BP and susceptibility to paradoxical pain. In a recent study, we identified rumination as a positive predictor of the occurrence of the TGI in healthy individuals (Scheuren et al, ). As an expression of poor emotional regulation, rumination involves the tendency to think repetitively and passively about situations causing negative emotions and to focus on symptoms of distress (Kubzansky, Davidson, & Rozanski, ).…”
Section: Discussionmentioning
confidence: 97%
“…The experimental procedure was comprised of a TG stimulation condition and two control conditions (CC1 and CC2; cf. Scheuren et al, ). Each condition included three stimulation blocks.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The overall reliability and validity of the PCS has been demonstrated in earlier studies26272829. Previous studies have demonstrated significant correlations with endogenous pain modulation and PCS303132, and the TGI and PCS33.…”
Section: Methodsmentioning
confidence: 73%